Autorzy:M.Dobrowolska
Wydawnictwo:GWO
Rok wydania:2015
Zapisz w jak najprostszej postaci 4.52 gwiazdek na podstawie 60 opinii

`a)\ 3(2x-1)+4(1-x)=ul(6x)-ul(ul(3))+ul(ul(4))-ul(4x)=2x+1`  

 

`b)\ 2(7x+5)-6(x-2)=ul(14x)+ul(ul(10))-ul(6x)+ul(ul(12))=8x+22` 

 

` ` `c)\ -2x(8-x)-5(x^2+3x)=ul(-16x)+ul(ul(2x^2))-ul(ul(5x^2))-ul(15x)=-3x^2-31x` 

 

`d)\ 5(3-2x)-(4x+6)*3=ul15-ul(ul(10x))-ul(ul(12x))-ul18=-22x-3` 

 

`e)\ 2x+5-(3x-12)/3=2x+5-(x-4)=ul(2x)+ul(ul(5))-ulx+ul(ul(4))=x+9` 

 

`f)\ (12x+16)/4-(10x+15)/5=(3x+4)-(2x+3)=ul(3x)+ul(ul(4))-ul(2x)-ul(ul(3))=x+1` 

 

`g)\ (9-6x)/3-(21-14x)/7=(3-2x)-(3-2x)=ul3-ul(ul(2x))-ul3+ul(ul(2x))=0` 

 

`h)\ (4(x-1))/2-3*(10x-50)/5=2(x-1)-3*(2x-10)=` 

`\ \ \ =ul(2x)-ul(ul(2))-ul(6x)+ul(ul(30))=-4x+28`